The State of Academic Administration at the National University in Laos - Vanengchue, Baysy; Thalungsy, Khamseng; Silavong, Nieo (ASEAN Journal of Educational Research and Technology, 2024)
The present research was conducted to investigate the current status of academic administration at the National University of Laos (NUOL), Lao PDR. It recognizes the important role of administration in ensuring the quality of education and needs to be understood. To achieve the objective, the survey questionnaire was employed to understand the status of the issue under investigation. The survey questionnaire was administered to 305 participants to seek their perceptions. The data were analyzed by using the SPSS program to find mean scores and standard deviations. Responses from the open-ended questions were analyzed by using content and thematic analysis. Its findings highlight important aspects of academic administration at NUOL such as curriculum implementation, learning and teaching management, learning and teaching media/materials, education quality assurance, and assessment and evaluation of learning outcomes. Furthermore, the survey results reveal that academics and lecturers expressed positivity towards each aspect of academic administration at NUOL. Therefore, for this issue to be fully and consistently practiced, ongoing support and follow-up activities must be in place.